The Role of Informatics in Cancer Personalized Medicine (International Journal of Engineering and Computer Science, 2015)
No doubt, significant number of people have been suffering from an adverse effects of medications especially that of traditional or self-medication to the extent that deaths occur. These effects happen as a result of mismatches of biological makeup of individuals taking these kinds of medications. This paper presents the state of the art of Personalized Medicine and Informatics in treatment of Cancer as well as some challenges the Informatics faces in Personalized Medicine in Cancer.